Condition-dependent male copulatory courtship and its benefits for females - Cargnelutti, Franco Ignacio (2021)
Postcopulatory sexual selection has shaped the ornaments used during copulatory courtship. However, we know relatively little about whether these courtship ornaments are costly to produce or whether they provide indirect benefits to females. We used the mealworm beetle, Tenebrio molitor, to explore this. We challenged males using an entomopathogenic fungus and compared their courtship (frequency of leg and antennal contacts to the female), copulation duration, number of eggs laid, and hatching rate against control males. Infected males copulated for longer yet they reduced their leg and antennal contacts compared to control males. However, there was no obvious relation between infection, copulation duration, and courtship with egg production and hatching success. In general, our results indicate that the ornaments used during postcopulatory courtship are condition-dependent. Moreover, such condition dependence cannot be linked to male fitness.